2022
DOI: 10.1186/s12877-022-03119-y
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' perspectives on rehabilitation and recovery one year after a hip fracture – a qualitative study

Abstract: Background In order to improve quality of care and recovery after hip fracture we need to include the perspectives of the individual older adults when evaluating different rehabilitation interventions. The aim of this study was therefore to explore older adults’ experiences of their rehabilitation after a hip fracture and of the recovery process during the 12 months following the fracture. Methods Qualitative interviews were conducted with 20 older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(63 reference statements)
0
3
0
2
Order By: Relevance
“…Nevertheless, the present results support the results of previous studies from different countries. [4][5][6]9,52,54,55,[67][68][69][70][71][72][73] An international survey would improve the external validity of our findings. Another potential limitation is that the opinions of patients with stroke and patients with fracture might have been overstated in the current sample.…”
Section: Limitationsmentioning
confidence: 77%
“…Nevertheless, the present results support the results of previous studies from different countries. [4][5][6]9,52,54,55,[67][68][69][70][71][72][73] An international survey would improve the external validity of our findings. Another potential limitation is that the opinions of patients with stroke and patients with fracture might have been overstated in the current sample.…”
Section: Limitationsmentioning
confidence: 77%
“…Postoperative social support from family and friends is crucial for satisfactory recovery after many orthopedic procedures. 41 Recovery after treatment is thus facilitated by both physical and psychosocial factors, which may contribute to the accelerated recovery in active older patients. Finally, a previous study 17 on DRFs found that hypertension is highly associated with complication rates after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors for earlier recovery may be related to psychosocial factors, such as motivation and rehabilitation efforts to return to preinjury activity levels. Postoperative social support from family and friends is crucial for satisfactory recovery after many orthopedic procedures . Recovery after treatment is thus facilitated by both physical and psychosocial factors, which may contribute to the accelerated recovery in active older patients.…”
Section: Discussionmentioning
confidence: 99%
“…La prevalencia de lesionados por AT tiene su pico a una edad joven entre los 20 y 30 años (16) , en nuestros resultados se pueden observar que por cada año que aumenta la edad existe mayor probabilidad de requerimiento de rehabilitación. Aunque no se haya encontrado información acerca de la necesidad de rehabilitación con la edad, esta cumple un rol importante cuando se habla de supervivencia y recuperación de lesiones en accidentes (17) . Los mayores de 60 años pueden tener hasta el doble de riesgo de fallecimiento por AT en comparación con la población menor de 60 años; dicha premisa también puede aplicarse al requerimiento de rehabilitación.…”
Section: Discussionunclassified
“…Aunque los jóvenes del sexo masculino son los principales causantes y víctimas, nuestros resultados mencionan que en las personas mayores de 60 años no existen diferencias entre el sexo de la víctima y el requerimiento de rehabilitación. Podrían existir diferencias a nivel hospitalario, incluyendo complicaciones y características específicas de las lesiones, como la osteoporosis y fractura de cadera en la mujer o las lesiones en extremidades y comorbilidades crónicas en el hombre (10,17) .…”
Section: Discussionunclassified